Book Review of Michael Brogan and David Spencer "Surviving Law School" - Bennett, Mark (Victoria University of Wellington Law Review, 2004)
Michael Brogan and David Spencer Surviving Law School (Oxford University Press, Melbourne, 2004) (294 + ix pages).